Russian Architectural Education: “Saw, Shura, It Is Gold…” - Meerovich, Mark (project baikal, 2017)
The article analyses the current situation in the architectural education concerning the changes in the way of acquiring information, the abundance of knowledge, the possibility to get a distance education, etc. The problems are formulated, and their solutions are proposed.